2017
DOI: 10.7575/aiac.alls.v.8n.6p.37
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Intercultural Competence of Thai University Students through Role-Play

Abstract: The current situation of international communication in globalization context requires intercultural competence (IC) to achieve successful communication (Crystal, 2003). Concerning this intercultural competence, non-verbal communication (NVC) plays a key role to indicate the success of having intercultural competence. On the other hand, Thai Ministry of Education (MOE) has launched the CEFR for the country policy in English teaching and learning (Ministry of Education, 2016). The purpose of this paper is to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Rodriguez and Caranza (2017) demonstrated that students' engagement in storytelling and intercultural projects were associated with their IC gains, i.e., deeper understanding of different cultural aspects and stronger bonds with students of diverse backgrounds. In a similar vein, Worawong, Charttrakul and Damnet (2017) showed that role-plays contributed considerably to more appropriate intercultural behaviors of the participants as manifested by their body movement, gestures and facial expressions in specific intercultural situations.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Rodriguez and Caranza (2017) demonstrated that students' engagement in storytelling and intercultural projects were associated with their IC gains, i.e., deeper understanding of different cultural aspects and stronger bonds with students of diverse backgrounds. In a similar vein, Worawong, Charttrakul and Damnet (2017) showed that role-plays contributed considerably to more appropriate intercultural behaviors of the participants as manifested by their body movement, gestures and facial expressions in specific intercultural situations.…”
Section: Literature Reviewmentioning
confidence: 81%
“…As research on intercultural communicative competence has progressed, so have its assessment methods. Contemporary assessment methodologies encompass a variety of approaches including self-report surveys, situational judgment tests, portfolios, and interactive role-plays tailored to intercultural contexts, as noted by Sinicrope et al (2007), and Worawong et al (2017). Given this array of assessment tools, there is an emerging necessity to amalgamate these varied methods within intercultural studies.…”
Section: Intercultural Communication Competence (Icc)mentioning
confidence: 99%
“…This includes conducting ethnographic interviews with the students' classmates or people from different cultures to explore intercultural interactions between local and international students (Arshavskaya, 2018), a Chinese TV drama to develop the intercultural competence of second language (L2), Chinese learners in Australia (Zhang, 2020), TV advertisements (Tirnaz & Narafshan, 2020), inviting guest speakers from other countries, classroom discussions and role-plays (Nakano, 2019), and using English textbooks to cultivate intercultural competence among Vietnamese university students (Quyen, 2018). In Thailand, attention has focused on adopting a teaching method and creating appropriate teaching materials to promote intercultural competence in English language classrooms, such as role-play (Noonkong et al, 2019;Worawong et al, 2017), English songs (Na Ayuthaya, 2018) and paintings (Wen, 2018). Notably, the large body of intercultural communication research in Thailand tends to be influenced by Anglophone culture (see Rattanapan et al, 2019;Suwannasom, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%